2016
DOI: 10.3389/fmars.2016.00215
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Trends in Polycyclic Aromatic Hydrocarbon (PAH) Contamination Assessed by 1-Hydroxypyrene in Fish Bile Fluid in the Netherlands: Declining in Marine Waters but Still a Concern in Estuaries

Abstract: Long-term monitoring data on the concentrations of biliary 1-hydroxypyrene (1-OHPyr) in flatfish, as a biomarker for polycyclic aromatic hydrocarbon (PAH) exposure, were analyzed and evaluated to elucidate spatial differences and temporal trends in marine and estuarine PAH contamination in the Netherlands. Dab (Limanda limanda) and flounder (Platichthys flesus) with partly overlapping distributions were used as target species. In total 1831 bile samples were analyzed individually: 417 dab in 1998-2005 and 143… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Our results mirror the UK status and trend assessment findings for bile metabolite in dab from the UK biogeographic regions, covering the period of 2010 to 2015, where PAHs were found to be unlikely to cause adverse biological effects (Nicolaus et al, 2018a). As also shown by other authors, PAH metabolites analysis in dab and flounder bile allowed to discriminate between distinctly impacted sampling sites (Richardson et al, 2001;Kammann, 2007;Devier et al, 2013;Vethaak et al, 2016), making it a reliable indicator of dab exposure to PAHs.…”
Section: -Oh Pyrenesupporting
confidence: 58%
See 1 more Smart Citation
“…Our results mirror the UK status and trend assessment findings for bile metabolite in dab from the UK biogeographic regions, covering the period of 2010 to 2015, where PAHs were found to be unlikely to cause adverse biological effects (Nicolaus et al, 2018a). As also shown by other authors, PAH metabolites analysis in dab and flounder bile allowed to discriminate between distinctly impacted sampling sites (Richardson et al, 2001;Kammann, 2007;Devier et al, 2013;Vethaak et al, 2016), making it a reliable indicator of dab exposure to PAHs.…”
Section: -Oh Pyrenesupporting
confidence: 58%
“…Well established biomarkers, such as hepatic EROD and biliary 1-OH pyrene have been shown to allow discriminating between distinctly impacted sampling sites, however factors such as season (sexual maturity), gender, nutritional status (condition factor) and age can affect these parameters in fish species used in monitoring programmes (Sleiderink et al, 1995b;Kammann et al, 2005;Kammann, 2007;Devier et al, 2013;Vethaak et al, 2016). There is however less work reported for other established biomarkers, like acetylcholinesterase inhibition for flatfish species (Kirby et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The levels of flounder bile hydroxypyrene showed that concentrations were 4 to 17 times higher, respectively, in Seine vs North Sea-Holland and in Seine vs Iceland (Kamman et al 2017). We suggest that the intensive dredging activities conducted in the Seine to maintain the navigation channel depth could be a major factor increasing the flounder contamination by PAHs in this estuary, as described in other industrial estuaries in Europe (Vethaak et al 2016).…”
Section: Fish Contamination By Metals and Organic Pollutantssupporting
confidence: 54%
“…The intraspecific variability is mainly explained by differences in body mass of fish. Indeed, the factors that determine the relative volume of fish bile include fish size, age, and gut fullness (Vethaak et al, 2016). We have found that the volume of bile per gram of fish was significantly and negatively correlated with gut fullness of fish.…”
Section: Volume Mass and Density Of Bilementioning
confidence: 74%